Regional Educational Performance Patterns in Europe - Péter Radó (Center for Educational Policy Studies Journal)
The paper aims to contribute to the assessment of the contextual relevance of various educational policies through an analysis of three aspects of the performance profiles of European countries: participation, the quality of learning outcomes and the equity of learning outcomes. Comparative analysis of international student achievement assessment surveys and statistical data reveals three European performance patterns: the compensative education systems of North and Northwest Europe, the selective education systems of Central Europe and the attritional education systems of Southeast Europe. On the basis of the identified performance patterns, the paper provides a brief outline of major trends within the Central and Southeast European regions, shares reflections on the alignment of policies that fit the distinct context of the two regions and offers a conceptual framework for further comparative research.